Skrining dan Edukasi Pencegahan Kelainan Postur Tubuh pada Anak Panti Asuhan - Hana Maria Uli Lumbanraja; Julfiana Mardatillah; Akhmad Ridhani; Hilda Emma Mallisa (Institut Nalanda, 2024)
The problem of posture abnormalities in children is increasingly becoming the center of attention. Poor habits in sitting position, standing posture and improper use of bags will cause posture abnormalities. Screening and education about the importance of maintaining posture has an important role in preventing postural abnormalities in children from an early age. This community service activity was carried out on 20 children at the Nur Azizah Putri Orphanage. At the beginning of this activity, screening was carried out first to see the condition of the child's posture, then providing education about efforts to prevent postural abnormalities. The method of implementing activities with lectures and demonstrations using power point media and posters. The screening results showed as many as 19 children with normal body conditions and 1 child leading to postural abnormalities. When providing education, children are very enthusiastic and excited. The results of the activity evaluation showed that all childrens were able to practice the correct sitting position, standing posture and use of bags in an effort to prevent postural abnormalities. With this activity, it is hoped that it can provide information for children at Nur Azizah Orphanage so that they can learn to maintain body balance to prevent and reduce postural risks in the future.